Perkembangan Filologi di Kawasan Timur Tengah - Arif Hidayatulloh (Tafhim Al-'Ilmi, 2019)
Egypt is important to be the object of research because it represents one of the universities considering those who are familiar with writing. In addition, according to Al-Hajiri, Egypt is a state of the Middle East (Arab) in the world of philology in modern times. This can be seen from the attention and philology activities carried out by Egyptian researchers who have preceded researchers from other Arab countries. During the Abbasiyah dynasty, in the government of Khalifahal-Mansur (754-775), HarunAlrasyid (786-809), and al-Makmun (809-833) manuscript studies and knowledge and knowledge about policy making, and policy developments related to the development of government al-Makmun. Hunain was one of the most prolific translators of the time and had the most knowledge. He mastered Arabic, Greek, and Syriac (syiria). The scientific activities carried out by Hunain bin Ishaq are quite interesting and very useful for other scientists. among others, inventorying any Greek manuscripts that have been translated into Syriac (Syrian) or Arabic, and other texts that have never been translated. Besides Hunain, the historical translator of classical works also replaced the names of great contemporary interpreters from Nestorian and Jacobite Christians such as Ibn Na'imah and al-Himshi (835 AD), Abu BisyrMatta (900 AD), Yahya bin Adi (974 AD ) and others. The only prominent Muslim translator today is Tsabit bin Qurra. Thanks to the dedication of these translators, Aristotle's logical thoughts were increasingly recognized and understood in the Arab world. Mesir penting untuk menjadi objek penelitian karena merupakan salah satu universitas yang akrab dengan tulisan. Selain itu, menurut Al-Hajiri, Mesir adalah negara Timur Tengah (Arab) di dunia filologi di zaman modern. Ini bisa dilihat dari perhatian kegiatan filologi yang dilakukan oleh peneliti Mesir daripada peneliti lainnya di negara-negara Arab lainnya. Selama dinasti Abbasiyah, pada pemerintahan Khalifah al-Mansur (754-775), Harun Alrasyid (786-809), dan studi naskah al-Makmun (809-833) dan pengetahuan tentang pembuatan kebijakan, dan perkembangan kebijakan terkait dengan pengembangan pemerintahan al-Makmun. Hunain adalah salah satu penerjemah paling produktif saat itu dan memiliki pengetahuan paling banyak. Dia menguasai bahasa Arab, Yunani, dan Syria (syiria). Kegiatan ilmiah yang dilakukan oleh Hunain bin Ishaq cukup menarik dan sangat bermanfaat bagi ilmuwan lain. antara lain, menginventarisasi naskah-naskah Yunani yang telah diterjemahkan ke dalam bahasa Syria (Syria) atau Arab, dan teks-teks lain yang belum pernah diterjemahkan. Selain Hunain, penerjemah historis dari karya-karya klasik juga menggantikan nama-nama penerjemah besar kontemporer dari Kristen Nestorian dan Jacobite seperti Ibn Na'imah dan al-Himshi (835 M), Abu BisyrMatta (900 M), Yahya bin Adi (974 M) ) dan lain-lain. Satu-satunya penerjemah Muslim terkemuka saat ini adalah Tsabit bin Qurra. Berkat dedikasi para penerjemah ini, pemikiran logis Aristoteles semakin diakui dan dipahami di dunia Arab. Keywords: Philology, development of the Arab World, Middle East, Egypt